2017
DOI: 10.1002/hbm.23803
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐specific neuromodulation of local and distant connectivity in aging and episodic memory function

Abstract: A growing literature has focused on the brain's ability to augment processing in local regions by recruiting distant communities of neurons in response to neural decline or insult. In particular, both younger and older adult populations recruit bilateral prefrontal cortex (PFC) as a means of compensating for increasing neural effort to maintain successful cognitive function. However, it remains unclear how local changes in neural activity affect the recruitment of this adaptive mechanism. To address this probl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 92 publications
(117 reference statements)
5
33
0
Order By: Relevance
“…How do age-related changes in synaptic plasticity, discussed below, affect DRT performance? Might neuromodulation (Arnsten et al, 2012;Davis et al, 2017;Wang et al, 2019) during working memory task performance reduce the pyramidal neuron hyperexcitability observed in vitro? Computational models provide an essential means for testing and refining hypotheses as future data become available.…”
Section: Discussionmentioning
confidence: 99%
“…How do age-related changes in synaptic plasticity, discussed below, affect DRT performance? Might neuromodulation (Arnsten et al, 2012;Davis et al, 2017;Wang et al, 2019) during working memory task performance reduce the pyramidal neuron hyperexcitability observed in vitro? Computational models provide an essential means for testing and refining hypotheses as future data become available.…”
Section: Discussionmentioning
confidence: 99%
“…Connectomes were generated by using FLIRT to apply a linear registration to a 471-region subparcellated version of the Harvard-Oxford atlas (HOA) (Davis et al, 2017) to register it to each subject's native diffusion space. The sub-parcellated HOA has the advantage of full cortical and subcortical coverage and relatively uniform, isometric ROI sizes.…”
Section: Dwi Data Processingmentioning
confidence: 99%
“…Davis et al (53) used rTMS at lower frequencies of either 1 or 5 Hz in the left DLPFC and did not identify any subsequent changes in word-pair association memory. Using functional Magnetic Resonance Imaging (fMRI), Davis et al did however find changes in neural activity following differing stimulation conditions.…”
Section: Associative Memorymentioning
confidence: 99%
“…A final 2 studies examined the effects of rTMS on associative memory performance (53,60). Manenti et al (60) applied rTMS (20 Hz) to either the left or right DLPFC during encoding or recalling of word-pairs and found that stimulation significantly impeded word-pair recall accuracy.…”
Section: Associative Memorymentioning
confidence: 99%